Pengaruh Inokulasi Jamur Mikoriza Arbuskular Terhadap Penyakit Busuk Pelepah Pada Jagung Di Lapangan - Soenartiningsih Soenartiningsih; Ambarwati Tj. Harsoyo; Nursamsi Pusposenjoyo; John Baco Baon (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
Sheath blight caused by Rhizoctonia solani is one of the important diseases in corn. A study on the effect of arbuscular mycorrhizal fungi in controlling sheath blight disease was conducted at pilot project scale in Jambangan Village, Malang District. Three-replicated treatments were arranged in a split-split plot design. The results showed that highest attack intensity occured at treatments without inoculation of arbuscular mycorrhizal fungi. The mean of attack intensity for Wisanggeni variety was 70,05%, while that for GM 30 line was 73,79%. The attack intensity at Wisanggeni variety inoculated with arbuscular mycorrhizal fungi was 45.39% to 49.46%, while that at GM 30 line was 47.52% to 56.12%. The infection of sheath blight disease reduced the production in terms of knob part and seed weight even though the plant was inoculated with arbuscular mycorrhizal fungi of Glomus sp. or Acaulospora mellea. The reduction of knob weight at Wisanggeni variety was 14.2% to 15.0% and that of seed weight was 21.4% to 23,0%. At GM 30 line the reduction of knob part was 12.0% to 17.2%, while that of seed weight was 19.1% to 20.4%.